Relación entre las actividades lúdicas y el fortalecimiento de la autoestima en estudiantes del nivel secundario de la institución educativa N° 6010189 Jesús de Praga, San Pablo 2024 - Alvarado Sandoval, Roldan (2025)
The aim of the present research was to determine relationship between recreational activities and strengthening of self-esteem in secondary level students of Educational Institution 6010189 Jesús de Praga, San Pablo, 2024, in response to question of problem: What is relationship between recreational activities and strengthening of self-esteem in secondary level students of Educational Institution 6010189 Jesús de Praga, San Pablo, 2024? For this, 114 students from the institution took part as both the population and the sample. The research was non experimental, and methodology of the study was correlational field. To collect data, the observation approach was used, with two questionnaires, one for each variable, which had been previously validated by experts. Results show that the Student's t test statistic = 6.89, with a bilateral significance of 0.001 and a confidence level of 95%, which confirms that there is a relationship between recreational activities in strengthening self-esteem in secondary level students of E.I. 6010189 Jesús de Praga, San Pablo, 2024, thereby testing the study hypothesis.